Embryogenic Callus as Target for Efficient Transformation of Cyclamen persicum Enabling Gene Function Studies - Ratjens, Svenja; Mortensen, Samuel; Kumpf, Antje; Bartsch, Melanie; Winkelmann, Traud (Frontiers in Plant Science, 2018)
Cyclamen persicum is an ornamental plant with economic relevance in many parts of the world. Moreover, it can be regarded as an applied model for somatic embryogenesis, since transcriptomic, proteomic, and metabolomic comparisons have revealed insights into this regeneration process on the molecular level. To enable gene function analyses, the aim of this study was to establish an efficient Agrobacterium tumefaciens-mediated genetic transformation protocol for C. persicum. For the first time, embryogenic callus cultures were used as a target material. The advantages of embryogenic callus are the defined and known genotype compared to seedlings, the high regeneration potential and the stability of the regenerated plants. A. tumefaciens strains EHA105 and LBA4404 were most efficient for transformation, resulting in transformation efficiencies of up to 43 and 20%, respectively. In regenerated plants, the presence of the transgenes was verified by PCR, Southern hybridization, and a histochemical GUS assay. The protocol was applied successfully to two C. persicum genotypes. Moreover, it served to transfer two reporter constructs, the auxin-responsive promoter DR5 driving the gus gene and the redox sensor roGFP2_Orp1, to the C. persicum genotypes, allowing the localization of high auxin concentrations and reactive oxygen species in order to study their roles in somatic embryogenesis in the future. For success in transformation, we regard the following factors as important: highly embryogenic cell lines, the use of Silwet® L-77 as a surfactant during co-culture, a genotype-specific appropriate selection schedule with hygromycin, and A. tumefaciens strains EHA105 and LBA4404.